Development of biochar using non-direct firing system from palm oil frond- physical characteristics / Nur Ilham Zainuddin - Zainuddin, Nur Ilham (2019)
Oil palm industry is the leading sector for Malaysia’s economy and become the largest exporter of palm oil worldwide and the second largest producer after Indonesia. The abundant of waste generated from oil palm industry in the year 2012 about 95.21 million tonnes of oil palm waste with the expectation in 2020 a serious waste management problems occur with approximately 88.74 Mt of biomass can be produced. During pruning period, the average of 4 kg per dry frond that lead to a total production of palm fronds around 5500 kg hectare per year. However, this highest abundance of OPF waste that has the potential to be converted into useful products though the environmental sustainability is still lacking. In this study, it aims to analyze the best parameter in preparing bio char from OPF and characterization of bio char based on its physical characteristics. This experiment is a batch experiments using a jacketed pyrolyzer applying non-direct firing system with 500 gram of palm frond biomass feed into the pyrolyzer. The heating rate was used at 20⁰C/min to rise into target terminal temperature at 400⁰C, 500⁰C and 600⁰C. The terminal pyrolysis temperature used effect the quality of bio char produced. The best temperature parameter for this experiment was found at 400 ⁰C which produced 16.071 m2/g of BET surface area, alkaline pH and porous structure compare to others two temperatures. Thus, it has potential to adsorb heavy metal contaminants with lower pyrolysis temperature, suitable for acidic soil and act as adsorbent. In this study, oil palm frond represents as a source for renewable energy and environment-friendly product.